The Role of Social Comparison and Body Image in Forming Appearance Anxiety in Adolescent Girls (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the role of social comparison and body image on appearance anxiety in adolescent girls. Social pressure and media exposure with ideal beauty standards make adolescent girls vulnerable to engaging in social comparison and developing a negative body image, which triggers appearance anxiety. This study used a quantitative approach with a correlational design involving 107 adolescent girls aged 18–24 years through convenience sampling. Data were collected using a Google Forms questionnaire consisting of three instruments: the Iowa-Netherlands Comparison Orientation Measure, the Multidimensional Body-Self Relations Questionnaire, and the Social Appearance Anxiety Scale. Data analysis used Spearman correlation and multiple linear regression. The results showed that social comparison has a significant positive relationship with appearance anxiety (r = 0.544, p < 0.001), and negative body image is related to increasing appearance anxiety. The higher the tendency to engage in social comparison and the more negative the body image, the higher the appearance anxiety experienced. The findings emphasize the importance of understanding the psychological dynamics of appearance evaluation and strategies to strengthen positive body image in adolescent girls.